Critique and Resistance in a Neoliberal Age : Towards a Narrative of Emancipation - Masquelier, Charles (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book lays the conceptual groundwork for a coalition of struggles under the neoliberal age. In doing so, the author demonstrates that, despite talk of fragmention, divisions and conflicts, the present situation offers fresh opportunities for connecting diverse solidarities. Critique and Resistance in a Neoliberal Age explores what connects individuals, not only between neoliberal conditions of economic, cultural and environmental domination but also in resistance. It also highlights the transformative power of human action, by grounding neoliberal processes in human action and demonstrating the relevance of, and opportunities for, emancipatory politics today. Offering a critique oriented towards social change, informed by a broad range of theoretical traditions and empirical research, the book will be of interest to students and scholars in the fields of sociology, politics and philosophy, as well as those interested in the possibilities for social change.- Resumé vydavatel
Keywords: neoliberalismus; svoboda -- politické aspekty; koalice; sociální změna; neo-liberalism; liberty -- political aspects; coalitions; social change; elektronické knihy; monografie; electronic books; monographs